Ozone ultrafine bubble water exhibits bactericidal activity against pathogenic bacteria in the oral cavity and upper airway and disinfects contaminated healthcare equipment - Fumio Takizawa; Hisanori Domon; Takumi Hiyoshi; Hikaru Tamura; Kana Shimizu; Tomoki Maekawa; Koichi Tabeta; Akiomi Ushida; Yutaka Terao (PLoS ONE, 2023)
Ozone is strong oxidizing agent that is applied in aqueous form for sanitation. However, ozonated water is unstable and has a short half-life. Ultrafine bubble technology is promising to overcome these issues. Ultrafine bubble is nanoscale bubble and can exist in water for a considerable duration of time. This study aims to investigate the application of ozone ultrafine bubble water (OUFBW) as a disinfectant. We produced an OUFBW generator which generates OUFBW containing 4–6 ppm of ozone. Thereafter, we examined the bactericidal activity of the OUFBW against various pathogenic bacteria in oral cavity and upper airway, including antibiotic-susceptible and antibiotic-resistant Streptococcus pneumoniae, Pseudomonas aeruginosa, Streptococcus mutans, Streptococcus sobrinus, Fusobacterium nucleatum, Prevotella intermedia, and Porphyromonas gingivalis. Exposure of planktonic culture of these bacterial species to OUFBW reduced viable bacteria by > 99% within 30s. Additionally, OUFBW exerted bactericidal activity against S. pneumoniae and P. aeruginosa adhered to toothbrush and gauze, respectively. We also observed disruption of bacterial cell wall of S. pneumoniae exposed to OUFBW by transmission electron microscope. Additionally, OUFB did not show any significant cytotoxicity toward the human gingival epithelial cell line Ca9‐22. These results suggest that OUFBW exhibits bactericidal activity against broad spectrum of bacteria and has low toxicity towards human cells.